Effect of Î±-tocopherol supplementation in chelation treatment on oxidative stress indices in erythrocytes of lead exposed calves - PATRA, R C; SWARUP, D; DWEVEDI, S K (The Indian Journal of Animal Sciences, 2014)
This study examined the possibility that supplementation of Î±-tocopherol with chelator calcium disodium EDTA. in the treatment of lead toxicity could reverse the lead-induced changes in the oxidative stress indices in the erythrocytes from lead exposed calves. One-month-old crossbred calves (15). were given lead daily @ 7.5 mg of 99% pure lead acetate/kg body weight orally for 28 day (group B). keeping another 5 calves as unexposed controls (group A). The leadexposed calves were randomly divided into 3 equal groups. Calves of group B1 were given no treatment to serve as positive controls. Those of group B1 were treated with 10% solution CaNa2 EDTA @ 110 mg/kg body weight in 2 divided doses daily through intravenouS route for 4 days. Calves of group B3 were given the same treatmentas that in group B2 together with a-tocopherol @ 100 mg/kg body weight orally daily for 7 days. Increase in the blood lead concentration was associated with a,significant increase in lipid peroxides level and nonsignificant decreases in the superoxid. dismutase and catalase activities in the erythrocytes. Irrespective of treatments, lipid peroxide levels returned to normalcy by day 2 of the start of the treatment. A significant increase in the erythrocytic catalase activity, compared to respectiw day 0 value, was observed by day 4 orthe start of the treatment, in group B2 and by day 2 in group B3 It was concluded that supplementation of Î±-tocopherol in chelation therapy had no significant effect on lipid peroxide level and activities of antioxidant enzymes in erythrocytes from lead-exposed calves.